Influence of TiO 2 and ZrO 2 nano particles addition in Al 2O 3 base coating using plasma spraying - Nuchjira Dejang (2018)
The additive (3wt%) nano-particles of anatase-TiO 2 and monoclinic-ZrO 2 were prepared using ball-milling method to form Al 2O 3/3wt%TiO 2 and Al 2O 3/3wt%ZrO 2 nanocomposite powders. The incorporation of nano-particles can significantly enhance the microstructure and mechanic properties of Al 2O 3-base coating. The phase of microstructure coating was present mostly of ?- Al 2O 3 and α- Al 2O 3 phases, while anatase-TiO 2 was transformed to rutile-TiO 2 and monoclinic-ZrO 2 was changed to tetragonal-ZrO 2 due to such high temperature of plasma plume. SEM microstructures of the coatings mainly displayed a lamellar structure of Al 2O 3 with interlarmellar pores and well dispersed splats of TiO 2 and ZrO 2 phases. The Al 2O 3/3wt%ZrO 2 presented the lowest value of friction coefficient and sliding wear rate. It was found that the plasma-sprayed composite coating possessed better wear resistance than that of monolithic Al 2O 3 coating. The addition of nano-particles was found to improve friction coefficient and sliding wear resistance. © (2012) Trans Tech Publications, Switzerland.